WHAT'S NEW WITH... - VNUK, REBECCA (Booklist, 2013)
The article discusses the strategic planning of reference publisher Gale, part of Cengage Learning, and quotes executive Ray Abruzzi. Electronic reference publishing, digital archives of material such as manuscripts, and the company's partnerships with museums and libraries, as well as 3-D imaging technology and the Artemis publishing line.